Long-term adaptive response of an oceanic diatom to copper deficiency - Kong, Liangliang; Price, Neil M. (Frontiers in Marine Science, 2022)
Enhanced vertical stratification brought about by warming of the ocean surface is expected to reduce vertical circulation and nutrient input with knock-on effects for phytoplankton. Increased nutrient limitation is one predicted outcome, but how that will impact phytoplankton is uncertain because we do not know how they will adapt. We used copper (Cu) as a model catalytic nutrient to explore the adaptive response of an oceanic diatom to continuous nutrient deprivation in laboratory experiments. Populations of Thalassiosira oceanica maintained under Cu-limiting and sufficient conditions for 380 generations differed significantly in their abilities to grow in medium containing 1 nM Cu. Continued selection for more than 2000 generations increased Cu use efficiency (CuUE) of a low Cu-adapted (LCuA) population by more than 2-fold compared to the control and ancestral populations. The increase in CuUE resulted from a decrease in the amount of cellular Cu required for growth and an increase in the net carbon assimilation rate. Redistribution of cellular Cu and increased efficiency of photosynthetic reactions are hypothesized to explain the fast rates of maximum electron transport of low Cu-adapted cells despite containing less Cu. The results show that adaptation increased resource use efficiency in phytoplankton, which could reduce the impact of increased nutrient deficiency in the future ocean.